Sepsis and acute kidney injury [Sepsis ve akut böbrek hasarı] - (:unkn) unknown (AVES Ibrahim Kara, 2014)
Acute kindney injury (AKI) is a clinical syndrome which is generally defined as an abrupt decline in glomerular filtration rate, causing accumulation of nitrogenous products and rapid development of fluid, electrolyte and acid base disorders. In intensive care unit sepsis and septic shock are leading causes of AKI. Sepsis-induced AKI literally acts as a biologic indicator of clinical deterioration. AKI triggers variety of immune, inflammatory, metabolic and humoral patways; ultimately leading distant organ dysfunction and increases morbidity and mortality. Serial mesurements of creatinine and urine volume do not make it possible to diagnose AKI at early stages. Serum creatinine influenced by age, weight, hydration status and become apparent only when the kidneys have lost 50% of their function. For that reason we need new markers, and many biomarkers in the diagnosis of early AKI activity is assessed. Historically “Risk-Injury-Failure-Loss-Endstage” (RIFLE), “Acute Kidney Injury Netwok” (AKIN) and “The Kidney Disease/ Improving Global Outcomes” (KDIGO) classification systems are used for diagnosing easily in clinical practice and research and grading disease. Classifications including diagnostic criteria are formed for the identification of AKI. Neutrophil gelatinase associated lipocalin (NGAL), cystatin-C (Cys-C), kidney injury molecule- 1 (KIM-1) and also “cell cycle arrest” molecules has been concerned for clinical use. In this review the pathophysiology of AKI, with the relationship of sepsis and the importance of early diagnosis of AKI is evaluated. © 2014 by Turkish Anaesthesiology and Intensive Care Society.
Keywords: Acute kidney injury; Biomarkers; KDIGO; RIFLE; Sepsis